Purity, power, and Pentecostal light the revivalist doctrine and means of Aaron Merritt Hills - Branstetter, C. J. (Christopher J.) (Eugene, Ore. : Pickwick Publications, 2012)
Around the turn of the twentieth century, revivalist Protestantism in America splintered into multiple pieces. Few persons of that era knew as many of the central figures of the splinter groups as Aaron Merritt Hills. Originally a Congregationalist who studied under Finney at Oberlin, Hills was a dyed-in-the-wool postmillennial revivalist until his death in 1935. While a Congregationalist, he befriended Reuben A. Torrey and made an enemy of Washington Gladden. In 1895 he joined the Holiness Movement after his experience of Spirit baptism. For the next forty years he founded colleges, held holiness revivals in both America and Britain, and wrote voluminously. While Hills himself is a lesser-known figure in the story of American Christianity, because of the many embroilments of his life, his story offers a unique window into the relationship between the Holiness Movement, Fundamentalism, Pentecostalism, American liberalism, and the Social Gospel Movement.
Hill's life and accomplishments -- The revivalist doctrine and spirit of post-bellujm Oberlin and Yale -- The early development of A.M. Hills' revivalist identity -- The tightening of A.M. Hills' revivalist canon -- The Hills controversies, or where does Hills fit?
Originally presented as the author's thesis (Ph. D.)--Drew University, 2006.
Includes bibliographical references (p. 259-263) and index.
Description based on print version record.
Keywords: Hills, A. M; Holiness movement; Holiness churches -- Clergy -- Biography; Holiness churches -- Doctrines; Revivals -- History; Evangelistic work -- United States; RELIGION / Messianic Judaism; Electronic books